Concepts Describing and Assessing Individuals’ Environmental Sustainability: An Integrative Review and Taxonomy - Wallnoefer, Laura M.; Riefler, Petra (Frontiers in Psychology, 2022)
The need to encourage individuals as active change agents for sustainability transitions has led researchers across disciplines to conceptualize over 70 constructs to assess relevant dispositions to environmental protection and green consumption behaviors. The generated knowledge is, however, fragmented by an unconsolidated set of constructs developed within literature streams. We, hence, use an integrative review method to capture conceptual and operational similarities and distinctiveness of constructs across disciplines, attempting to unify the knowledge base. Thereby, we identify 34 conceptually distinct constructs (along with 38 synonyms and 76 scales) relevant to our thematic synthesis on individual-level constructs framing contributions to environmental measures and issues. We followingly propose a taxonomy, systemizing constructs based on their concept type(s) (e.g., value, attitude, behavior) and contextual scope(s) of the environmental challenge (e.g., product choice, household practice) addressed. We capture these dimensions in critically assessing relevant and salient conceptual and operational features. We thus create a consolidated picture of extant constructs capturing individual-level environmental sustainability by which we intend a three-fold contribution to the interdisciplinary field. First, the taxonomy and guiding framework for the choice of constructs should assist substantive researchers in identifying appropriate constructs of interest. Second, the systematic integration of (dis)similar concepts available in parallel disciplines should assist future endeavors aiming at integrating substantive findings with regard to antecedents, consequences, and other relevant variables. Finally, the taxonomy revealed that conceptualizations mainly scatter around specific combinations of types and scopes while others remain unaddressed. Based on our critical assessment of the relevant features and resulting taxonomy, we identify avenues for future research dedicated to (i) enhancing conceptual rigor and measurement quality in the field and (ii) introducing concepts addressing missing but potentially valuable combinations of types and scopes (e.g., antecedents capturing green consumption contexts). We conclude that researchers engaging in the proposed avenues with conceptual, methodological, or empirical contributions should consider four critical aspects to advance knowledge accumulation and prevent fragmentation in the interdisciplinary field. We thereby hope to pave the way for a collective, interdisciplinary knowledge base of concepts used to describe and assess individual’s pro-environmental dispositions and practices of green consumption.